New record of the boxelder bug Boisea trivittata in Argentina suggests a rapid spread - Aragon y Traverso, Juan Héctor (2025)
This study documents the presence of the boxelder bug Boisea trivittata (Say, 1825) (Hemiptera: Rhopalidae) in the city of San Juan, Argentina. In May 2024 (austral autumn), twelve specimens of B. trivittata were identified and deposited in the collection of the Institute of Basic Sciences at the National University of San Juan. This species, native to North America, is not considered a pest in its native range, and its introduction to South America was first reported in Santiago, in 2020. Our record adds to the first report of the species in Argentina, documented in the city of Mendoza in April 2024. This study provides relevant information on the species and discusses potential management strategies.